2011
DOI: 10.1007/s12640-011-9297-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Exercise on Traumatic Brain Injury Deficits: Scaffolding Effect

Abstract: Traumatic brain injury (TBI) may be due to a bump, blow, or jolt to the head or a penetrating head injury that disrupts normal brain function; it presents an ever-growing, serious public health problem that causes a considerable number of fatalities and cases of permanent disability annually. Physical exercise restores the healthy homeostatic regulation of stress, affect and the regulation of hypothalamic-pituitary-adrenal axis. Physical activity attenuates or reverses the performance deficits observed in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 234 publications
(205 reference statements)
1
46
0
Order By: Relevance
“…Recent reviews of the literature support the benefits of exercise as an active rehabilitation treatment when postconcussion symptoms persist beyond the expected recovery period after injury [20, 21, 25, 26]. Indeed, it has been postulated that the introduction of physical activity may have a positive impact on the chronic symptoms following mTBI [17, 24, 2742]. Preliminary evidence demonstrated that exercise, when used as a treatment, reduces reported symptoms in adults [17, 18, 22, 43, 44] and in youth who are slow-to-recover after mTBI [9, 35, 45].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of the literature support the benefits of exercise as an active rehabilitation treatment when postconcussion symptoms persist beyond the expected recovery period after injury [20, 21, 25, 26]. Indeed, it has been postulated that the introduction of physical activity may have a positive impact on the chronic symptoms following mTBI [17, 24, 2742]. Preliminary evidence demonstrated that exercise, when used as a treatment, reduces reported symptoms in adults [17, 18, 22, 43, 44] and in youth who are slow-to-recover after mTBI [9, 35, 45].…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical exercise has been proved to have therapeutic benefit [1], such as treating psychiatric illnesses [2,3,4,5,6,7], supporting brain injury recovery [8,9,10,11,12], and resisting neurodegenerative diseases [13,14,15,16,17,18]. The advantageous effects of exercise on brain functions have been attributed to increased capacities of metabolism reserve and antioxidation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…pro-inflammatory cytokines and cortisol. Taking into account, the large proportion of individuals with more-or-less sedentary preoccupations, physical exercise presents uniquely one of the most potent health-promoting lifestyles available by rendering positive outcomes for both neurologic and psychiatric conditions [10][11][12][13][14][15]. It is beneficial also within domains defined by neurocognitive capacity, quality-of-life, postural and motor efficacy and affective status [16][17][18].…”
Section: Editorialmentioning
confidence: 99%